IJCM_226A: Bridging the Gap: Model Immunization Centers in Urban Bihar - A Study on Factors Shaping Community Acceptance and Utilization for Improved Immunization Coverage - Rauny Rahul; Sinha N.K; Dhalaria Pritu; Agrawal Ayushi; Verma Anupam; Singh Ajeet; JSI Syed Hassan (Wolters Kluwer Medknow Publications, 2024)
Background: Despite significant strides in immunization coverage, Full Immunization coverage in urban areas of India lags behind rural regions, with Urban India recording 75.5% compared to 76.8% in rural areas. Additionally, the prevalence of zero-dose children is higher in Urban India (7.5%) compared to rural counterparts (6.3%). Urbanization introduces a complex dynamic marked by poverty, migration, and growing disparities in health access, social services, and economic resources that necessitate innovative strategies to address immunization inequities in urban settings. In this direction, the Government of Bihar in 2017 introduced the concept of Model Immunization Centers (MICs) to provide high-quality immunization services to urban poor and marginalized to improve coverage and build trust, confidence and motivation for public immunization services. Objectives: The primary objective of the study was to assess and identify the factors that shape the community's acceptance and utilization of immunization services at MICs in Patna and Siwan. Methodology: A mixed-methods approach was employed, combining quantitative data analysis of immunization records and demographic information with qualitative assessments of community perceptions through in-depth interviews and focus group discussions. The study site i.e., Patna and Siwan Districts of Bihar was purposively selected. Results: The study found that the effectiveness of MICs was significantly influenced by family, community, and social norms. Additionally, MICs played a pivotal role in enhancing people's trust, confidence, and motivation through the provision of a favourable environment, hygiene maintenance, the availability of free vaccines, reduced waiting times, and courteous staff behaviour. These factors have collectively led to improved immunization coverage, increased footfall, and improved rates of full immunization. Conclusion: The success of MIC in gaining people's trust and confidence has been a driving force behind the increase in footfall coverage at session sites and high Full Immunization Coverage in Patna and Siwan